2020
DOI: 10.1186/s40662-020-00215-1
|View full text |Cite
|
Sign up to set email alerts
|

Tomography-based definition of keratoconus for Down syndrome patients

Abstract: Background To assess the diagnostic ability of Pentacam HR (Oculus Optikgeräte, GmbH, Wetzlar, Germany) tomographic indices in discriminating keratoconus (KC) and KC suspect (KCS) in 10- to 30-year-old patients with Down syndrome (DS). Methods In this study, DS patients were enrolled through special needs schools, the National Down Syndrome Society, and relevant non-profit organizations. Diagnoses were made independently by two exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
0
8
2
Order By: Relevance
“…The 30 AC patients in our study could not be diagnosed with KC because none had the typical clinical signs specific for KC. However, according to the tomographic criteria for KC diagnosis as described by Asgari [ 29 ], including Kmax > 48.0 D, ART-max < 339 μm, I-S value > 1.4 D, BAD-D > 1.6, and posterior elevation, 8 patients in our study met the tomographic criteria for KC. Among them, 1 patient met three criteria (ART-max, I-S value and BAD-D), 2 patients met two criteria, and the other 5 patients met one criterion.…”
Section: Discussionmentioning
confidence: 63%
“…The 30 AC patients in our study could not be diagnosed with KC because none had the typical clinical signs specific for KC. However, according to the tomographic criteria for KC diagnosis as described by Asgari [ 29 ], including Kmax > 48.0 D, ART-max < 339 μm, I-S value > 1.4 D, BAD-D > 1.6, and posterior elevation, 8 patients in our study met the tomographic criteria for KC. Among them, 1 patient met three criteria (ART-max, I-S value and BAD-D), 2 patients met two criteria, and the other 5 patients met one criterion.…”
Section: Discussionmentioning
confidence: 63%
“…In fact, due to these similarities, it is very difficult to discriminate mild KC from the normal pattern in DS patients. In a previous report (13), we showed that among corneal indices, MCT, corneal volume, and BAD-D had a relatively good diagnostic ability in DS patients and the diagnostic power of these indices for detecting KC was not as excellent as their power in non-DS subjects. Also, HOA and coma were the best discriminators.…”
Section: Female Male Mean ± Sd 95% CI Median Mean ± Sd 95% Ci Medianmentioning
confidence: 71%
“…In particular, these patients have thinner and steeper corneas than healthy individuals, which likely contributes to the development of keratoconus in this population. 71 , 84 , 85 Haugen and Hovding 40 previously examined a young adult population of patients with Down syndrome and found a reduced corneal thickness (0.48 ± 0.04 mm; range 0.40–0.57) compared to the general population (0.55 ± 0.03 mm; range 0.49–0.64). Furthermore, they found higher keratometry values, thinner lenses, and weaker lens power compared to controls.…”
Section: Keratoconusmentioning
confidence: 99%
“…The authors also proposed that topographical tools may be of import in developing diagnostic criteria for Down syndrome patients. 84 …”
Section: Topographical Screening Toolsmentioning
confidence: 99%
See 1 more Smart Citation